2022
DOI: 10.1128/jvi.00257-22
|View full text |Cite
|
Sign up to set email alerts
|

A System Based on Novel Parainfluenza Virus PIV5-L for Efficient Gene Delivery of B-Lymphoma Cells

Abstract: B-cell lymphoma is a common aggressive neoplastic disorder of lymphocytes. Delivery of genes of interest into B cells, particularly virus-mediated B-lymphoma cells, is still a challenge. In this study, we report that a system (L-VLP) based on the parainfluenza virus PIV5-L strain isolated from B cells had highly expressed exogenous genes and remained stable without obvious cell toxicity, which provides a potential new strategy for gene delivery and treatment of B-cell cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…These observations support the growing body of studies that identifies VLPs as a intriguing system for targeted therapies: several models have been developed not only in vaccination strategies, where the expression of selective antigen domains elicit the production of neutralizing antibodies ( Zha et al., 2021 ), but also for the delivery of therapeutic molecules by expressing ligands for specific receptors overexpressed in tumor cells ( Pokorski et al., 2011 ; Kitai et al., 2011 ; Galaway and Stockley, 2012 ; Liu et al., 2022 ) or for gene editing applications ( Banskota et al., 2022 ). Overall, in this study we have demonstrated several key points that make the VLPs-M8 system a promising platform for a potential clinical use: I) Inclusion – we demonstrated that HIV-1 - based packaging system incorporated and protected M8 for intracellular release; II) Delivery M8 was efficiently transferred to target cells where it triggered a RIG-I – dependent type-I IFN response that drastically reduced or completely blocked viral replication; III) Versatility and Specificity – one of the most important advantages of this system is its flexibility; indeed VLPs surface modifications guide VLPs to a selective cell population expressing a specific receptor.…”
Section: Discussionsupporting
confidence: 56%
“…These observations support the growing body of studies that identifies VLPs as a intriguing system for targeted therapies: several models have been developed not only in vaccination strategies, where the expression of selective antigen domains elicit the production of neutralizing antibodies ( Zha et al., 2021 ), but also for the delivery of therapeutic molecules by expressing ligands for specific receptors overexpressed in tumor cells ( Pokorski et al., 2011 ; Kitai et al., 2011 ; Galaway and Stockley, 2012 ; Liu et al., 2022 ) or for gene editing applications ( Banskota et al., 2022 ). Overall, in this study we have demonstrated several key points that make the VLPs-M8 system a promising platform for a potential clinical use: I) Inclusion – we demonstrated that HIV-1 - based packaging system incorporated and protected M8 for intracellular release; II) Delivery M8 was efficiently transferred to target cells where it triggered a RIG-I – dependent type-I IFN response that drastically reduced or completely blocked viral replication; III) Versatility and Specificity – one of the most important advantages of this system is its flexibility; indeed VLPs surface modifications guide VLPs to a selective cell population expressing a specific receptor.…”
Section: Discussionsupporting
confidence: 56%
“…69 This hypothesis was further supported by theoretical and experimental evidence, including strains isolated from a variety of human tissues on numerous occasions. [76][77][78] A recent report showed that a novel PIV5 strain was isolated from a lesser panda, which was closely related to the zoo tiger PIV5 strains isolated in China in 2015 and 2018. 79 Subsequently, two more PIV5 strains were identified in pangolins in China.…”
Section: Genomic Diversity Of Piv5 Strainsmentioning
confidence: 87%
“…Based on this, it was speculated that infection of monkeys may occur either in transit or shortly after contact with humans 69 . This hypothesis was further supported by theoretical and experimental evidence, including strains isolated from a variety of human tissues on numerous occasions 76–78 …”
Section: The Biological Features Of Piv5mentioning
confidence: 91%
See 2 more Smart Citations